Erythropoietin ameliorates chemotherapy-induced toxicity in vivo - Sigounas, George; Mehlhop, Paul (My University, 2002)
A method of reducing organ toxicity in a subject being administered a cytotoxic agent comprising concurrently administering with the cytotoxic agent erythropoietin (EPO), the EPO being administered in an amount effective to reduce pulmonary toxicity caused by the cytotoxic agent.
Application abandoned?
Keywords: cytotoxicity